PEMANFAATAN TANDAN KOSONG KELAPA SAWIT SEBAGAI MEDIA TANAM JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Fitria Nugraheni Sukmawati (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2018)
Pleurotus ostreatus is one of wood fungus whose easier to cultivated, because it has good adaptability to grow. The use of oil palm empty bunches (tankos) as a medium for the growth of Pleurotus ostreatus was carried out to determine the effect of tankos as a medium on Pleurotus ostreatus yield. The experiment was conducted at the Production House of Pleurotus ostreatus Desa Cerme, Grogol, Kediri. This experiment was used non factorial Randomized Complete Block Design consisting of 5 treatments which is the ratio of tankos and sawdust for medium, there are 0%:100%; 25%:75%; 50%:50%; 75%:25%; and 100%:0%. The results showed that tankos potential as a medium for Pleurotus ostreatus, as indicated by the content of lignin, cellulose, and hemicellulose which are nutrients for growth and development fungal, the higher the composition of the tankos, the higher the nutrient content. The observations for the hood diameter, harvest interval, and wet weight were best in the composition treatment of 50% Tankos: 50% Sawdust. Keywords: tankos, medium, fungus